Aging of Attentiveness in Border Collies and Other Pet Dog Breeds: The Protective Benefits of Lifelong Training - Chapagain, Durga; Virányi, Zsófia; Wallis, Lisa J.; Huber, Ludwig; Serra, Jessica; Range, Friederike (Frontiers in Aging Neuroscience, 2017)
Aging of attentiveness affects cognitive functions like perception and working memory, which can seriously impact communication between dogs and humans, potentially hindering training and cooperation. Previous studies have revealed that aged laboratory beagles and pet Border collies show a decline in selective attention. However, much less is known about the aging of attentiveness in pet dogs in general rather than in specific breeds. Using 185 pet dogs (75 Border collies and 110 dogs of other breeds) divided into three age groups (late adulthood (6- <8 yr), senior (8- <10 yr) and geriatric (≥10yr)), we assessed the progress of aging of attentional capture, sustained and selective attention in older dogs in order to explore if prior results in Border collies are generalizable and to evaluate the influence of lifelong training on measures of attention. Each dog’s lifelong training score (ranging from 0 to 52) was calculated from a questionnaire filled in by the owners listing what kinds of training the dog participated in during its entire life. Dogs were tested in two tasks; the first, measuring attentional capture and sustained attention towards two stimuli (toy and human); and the second, measuring selective attention by means of clicker training for eye contact and finding food on the floor. In the first task, results revealed a significant effect of age but no effect of lifelong training on latency to orient to the stimuli. Duration of looking decreased with age and increased with lifelong training. In the second task, while lifelong training decreased the latency of dogs to form eye contact, aged dogs needed longer to find food. Border collies did not differ from other dogs in any measures of attention except latency to find food. In conclusion, aged dogs showed a decline in attentional capture and sustained attention demonstrating that these tests are sensitive to detect aging of attentiveness in older pet dogs. Importantly, selective attention remained unchanged with age and lifelong training seemed to delay or reduce the aging of attentiveness, further highlighting the importance of lifelong training in retaining general cognitive functions.